2020
DOI: 10.3390/s20041117
|View full text |Cite
|
Sign up to set email alerts
|

High-Precision Acceleration Measurement System Based on Tunnel Magneto-Resistance Effect

Abstract: A high-precision acceleration measurement system based on an ultra-sensitive tunnel magneto-resistance (TMR) sensor is presented in this paper. A “force–magnetic–electric” coupling structure that converts an input acceleration into a change in magnetic field around the TMR sensor is designed. In such a structure, a micro-cantilever is integrated with a magnetic field source on its tip. Under an acceleration, the mechanical displacement of the cantilever causes a change in the spatial magnetic field sensed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Compared with the TMR gyroscope in Literature [ 18 ] with a noise floor of 9.48 × 10 −5 °/s/ , that of our design reduced by 12.29 times. Simultaneously, the magnetic film used in Literature [ 17 , 21 ] has a mT-level MII and a mT/mm-level magnetic sensitivity, while the permanent magnet used in Literature [ 18 , 22 ] have a T-level MII and an oe/um-level magnetic sensitivity. All of them require a large-range TMR unit to detect the variation of magnetic field such as TMR 2105 and TMR P44FP, or a higher detection gap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the TMR gyroscope in Literature [ 18 ] with a noise floor of 9.48 × 10 −5 °/s/ , that of our design reduced by 12.29 times. Simultaneously, the magnetic film used in Literature [ 17 , 21 ] has a mT-level MII and a mT/mm-level magnetic sensitivity, while the permanent magnet used in Literature [ 18 , 22 ] have a T-level MII and an oe/um-level magnetic sensitivity. All of them require a large-range TMR unit to detect the variation of magnetic field such as TMR 2105 and TMR P44FP, or a higher detection gap.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results indicated that the final sensitivities of the two devices are 409.01 mV/g and 8.85mV/g, respectively. Literature [ 22 ] reported another accelerometer with the similar operating principle to ones from [ 17 , 21 ]. The peculiarity of latter one is the use of the simpler but more effective micro-cantilever sensing structure, and the test results demonstrated the system could achieve measurement resolution of 17.35 µg/ .…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in magnetic field sensor fabrication technologies introduced new IC types of magnetic field sensors that can be used in contactless current transducers. These sensors are based on the MR (Magnetoresistance) effect [ 11 , 12 , 13 ]. MR IC sensors are used for low magnetic field detection since their sensitivities are extremely high, but they saturate at low magnetic field levels compared to Hall sensors [ 4 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%